To compare the effectiveness of oral azithromycin versus intravenous ceftriaxone for treating uncomplicated enteric fever - Sreenivasa, B; Manjunatha, B; Joseph, Nivil (Indian Journal of Child Health, 2016)
Objectives: To compare the clinical effectiveness of oral azithromycin versus intravenous (IV) ceftriaxone for treating uncomplicated enteric fever. Methods: Children aged 2-17 years with uncomplicated enteric fever and positive blood cultures for Salmonella typhi were included in the study. These were grouped as Group A (50 cases) and Group B (50 cases). Group A was given oral azithromycin 10 mg/kg/day once a day (azithromycin group) and Group B was given IV ceftriaxone 100 mg/kg/day in 2 divided doses (ceftriaxone group) for 6 and 7 days, respectively. Every day the child was examined, and the study results were assigned as a clinical and microbiological cure or failure. Results: A total of 100 patients in sex ratio of 1.2:1 (male:female) with uncomplicated enteric fever were enrolled in the study. Mean duration to become afebrile was less with azithromycin (2.72 days) as compared to ceftriaxone (5.52 days) treatment (p=0.000). 96% of the cases treated with azithromycin attained defervescence by the 5th day of treatment, but only 27% of cases treated with ceftriaxone attained defervescence by the 5th day of treatment. A clinical cure was earlier with azithromycin than with ceftriaxone treatment (p=0.027). Microbiological cure was achieved in 100% and 98% cases treated with azithromycin and ceftriaxone, respectively (p=0.5). Conclusion: Oral azithromycin was more efficacious in the treatment of uncomplicated enteric fever in children as compared to IV ceftriaxone.